(untitled) (Research, Society and Development, 2022)
Dermatopathies represent about 30% of the visits performed in the clinical routine of small animals. Among the parasitic dermatopathies, scabies represents 7.3% of the cases, being characterized by intense itching, scaling, erythema, skin rashes and crusted lesions; it is also a disease of high relevance due to its high zoonotic potential. The present study aimed to report the clinical, epidemiological and therapeutic aspects of sarcoptic mange in cats diagnosed in the metropolitan region of Joao Pessoa, Paraiba, Brazil. The animals were submitted to clinical, dermatological exams, such as skin scrapings. The distribution of lesions focused on classic anatomical sites such as the face, ear and nasal plane. After confirming the diagnosis, the animals were treated with spot-on selamectin in a single dose and after 30 days the cats no longer presented pruritus or crusty lesions.